JAK-1/STAT-3 pathway mediated role in aging cerebellar cortex degenerative changes of albino wistar rats - Ahmed S. Ahmed (Elsevier, 2021)
Background: Glial fibrillary acidic protein (GFAP) is considered an important component of cerebellar astrocyte cytoskeleton. Previous studies had shown that the amount of GFAP may increase in all aging brain zones reflecting underlying gliosis. JAK-STAT system carry signals to deoxyribonucleic acid (DNA) affecting genes transcription. Different zones of the human brain accumulate Alzheimer's Disease (AD) pathological markers but cerebellum is proved to be the least affected zone. Aim: The aim of the present research is to explore the impact of JAK-1/STAT-3 pathway on aging process of rats' cerebellar cortex. Method: Sixty albino Wistar rats were divided into 12 M, 24 M and 32 M groups aged twelve, twenty-four and thirty-two months respectively. After one week of acclimatization, cerebella were dissected under general anesthesia and collected for histopathological examination, western blotting and biochemical examination. Results: Degenerative changes were noticed in the cerebellum in addition to a significant decrease of thickness of all cerebellar layers thickness except granular layer in both 24 M and 32 M groups which also showed moderate and sever GFAP immunoreaction respectively. In 24M-group purkinje cells showed irregular nuclear envelope with disturbed mitochondrial cristae while in 32M-group, purkinje cells showed a greater extent of nuclear envelop irregularity and myelin sheath of granular cells axons appeared splitted. 12 M, 24 M and 32 M groups showed mild, moderate and sever caspase-3 immunoreaction. There was a significant decrease in JAK-1, STAT-3 and GSH expression in 24 M and 32 M groups while SOCS-3, TNF-α and MDA expression increased in the same groups which denotes the occurrence of cerebellar inflammatory pathway linked to aging. Conclusion: JAK-1 and STAT-3 activity increase or SOCS-3 activity decrease can protect against cerebellar insult associated with aging cerebellum.